RATIONALISING THE LOCATION AND DESIGN OF THE WASTE DUMP IN THE CASE OF OPEN-PIT MINING - Dimitar Kaykov; Ivaylo Koprev (Sustainable Extraction and Processing of Raw Materials Journal, 2020)
ABSTRACT. The location for dumping the waste from the open–pit mine has a significant weight for the establishment of the waste treatment costs. According to the constructive parameters of the waste dump and the terrain’s characteristics, the volume of the affected area is determined, in relation to the waste volume generated from the exploitation of a mineral deposit. In order to optimise the waste dump’s location and its constructive parameters, a number of alternatives have to be taken into account. These alternatives have to be technically plausible, as well as their safety factor must be satisfactory. Based on the considered alternatives, the optimisation problem can be defined so that the optimal solution provides the required capacity of the waste dump, as well as a minimal area of negative environmental impact and lowest operational costs.